2012
DOI: 10.1063/1.4758475
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of SnF2+, SnCl2+, and SnO2+ and their experimental search

Abstract: We present a detailed theoretical study of the stability of the gas-phase diatomic dications SnF(2+), SnCl(2+), and SnO(2+) using ab initio computer calculations. The ground states of SnF(2+), SnCl(2+), and SnO(2+) are thermodynamically stable, respectively, with dissociation energies of 0.45, 0.30, and 0.42 eV. Whereas SnF(2+) dissociates into Sn(2+) + F, the long range behaviour of the potential energy curves of SnCl(2+) and SnO(2+) is repulsive and wide barrier heights due to avoided crossing act as a kind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…For diatomic molecules involving light atoms up to Ar, the characterization of the electronic structure and the spectroscopic parameters of the ground and excited states is well established by the use of multireference methodologies. These approaches have successfully predicted the properties of the ground and excited electronic states for the main group elements investigated lately. Most of these studies were carried out using the internally contracted MRCI ( ic -MRCI, see section ). Sivalingam et al have compared the performance of this method for the ground and excited states of selected diatomic molecules with the strongly contracted MRCI (SC-MRCI) method, showing that the two methods are bounded from below by the uncontracted MRCI ( uc -MRCI).…”
Section: Applications Of Multireference Methods To Molecular Excited ...mentioning
confidence: 99%
“…For diatomic molecules involving light atoms up to Ar, the characterization of the electronic structure and the spectroscopic parameters of the ground and excited states is well established by the use of multireference methodologies. These approaches have successfully predicted the properties of the ground and excited electronic states for the main group elements investigated lately. Most of these studies were carried out using the internally contracted MRCI ( ic -MRCI, see section ). Sivalingam et al have compared the performance of this method for the ground and excited states of selected diatomic molecules with the strongly contracted MRCI (SC-MRCI) method, showing that the two methods are bounded from below by the uncontracted MRCI ( uc -MRCI).…”
Section: Applications Of Multireference Methods To Molecular Excited ...mentioning
confidence: 99%
“…The single-reference CC hierarchy breaks down whenever a single determinant becomes an improper zeroth-order description of the system, whereas multireference methods lack a systematic hierarchy comparable to CC theory. The standard schemes, beyond second-order perturbation theory, still rely on multireference configuration interaction (MRCI) with approximate size-extensivity corrections. The extension of coupled-cluster theory to multireference cases, on the other hand, is not straightforward, and only recently have a number of implementations been reported that are capable of treating realistic systems. In this context, the multireference coupled-cluster (MRCC) theory , should provide a very reliable way to treat systems with such complex electronic structure.…”
Section: Introductionmentioning
confidence: 99%